Sleep characteristics in Goldenhar Syndrome. Issue 3 (March 2015) - Baugh, A.D.; Wooten, W.; Chapman, B.; Drake, A.F.; Vaughn, B.V.
Abstract Objective To examine the characteristics of sleep in patients with Goldenhar Syndrome. Design Retrospective review of all polysomnography studies conducted at the University of North Carolina Hospitals between 2003 and 2013 on patients carrying the diagnosis of Goldenhar's Syndrome. Results A preponderance of patients demonstrated severe obstructive sleep apnea and hypercapnia. Conclusions Patients with Goldenhar Syndrome should be screened for sleep apnea and hypercapnia.